"The Signs of Heaven to Ken": Astrological Lore and Spenser's - Richardson, John Michael (My University, 1983)
This thesis argues that Spenser•s handling of character, situation, and theme throughout The Shepheardes Calender corresponds to the traditional significations of the planetary and zodiacal governors of the twelve eclogues. The introductory chapter outlines some fundamental principles of the two astrological traditions relevant to the present study, traditions that I have loosely called Ptolemaic or "Scientific" and Neoplatonic, and explains that the lack of horoscopal information about the characters constitutes no serious barrier to my approach. To avoid the repetition that would result from organizing the study around zodiacal signs, I have used a planet-by-planet approach. Chapter I analyses Colin Clouts past achievements and his present predicament in terms of two distinct but related conceptions of Saturn and melancholy: its main argument is that Colin's early accomplishments align him with a benevolent Saturn and with what Yates calls inspired melancholy (based ultimately on the "Aristotelian" Physical Problems XXX), the earthly Venus leads him in a contrary direction, and the frustration of this Venerean impulse makes him a victim of the malevolent Saturn of popular astrology. Chapter II argues that in "Februarie", ruled by Jupiter, a mean between Saturn and Venus, the conflict between the malevolent Saturn and the earthly Venus reappears in the debate between a Saturnian Thenot and a Venerean Cuddie, and that since all figures in the debate and the tale are "failed Jupiters" , the conflict ends in a deadlock aptly corresponding to the fact that the fish of Pisces move in opposite directions, but within the same element, and are bound by a common cord. In "November", however, Dido is a true Jovial figure, and the Jovial aspects of the eclogue's context temporarily dispel Colin's Saturnian gloom and cooperate with the benevolent Saturn to lift Colin's mind "above the starry skie", a movement appropriate to the significations of the centaur figure Sagittarius. Chapter III shows that Spenser accommodates Mars in his Calender: by parodic reduction in "March" and by evoking Mars in "October" to point beyond the pastoral to his projected epic. The Venus inherited by the Renaissance represents a vast range of ideas about love and beauty, from the basest carnality through to the principles of cosmic harmony and the most mystical expressions of love for God. Chapter IV discusses the correspondences between several of these significations and the eel ogues for Venus' two signs, Taurus ("April") and Libra ("September"): in addition to discussing Colin's misadventure in love, this chapter demonstrates "April's" suitability for a celebration of the encomiastic poet; discusses the manifestations of Venus that are in harmony with the benevolent Saturn; examines Eliza's role as a Venus figure presiding over an idyllic natural, political, and poetic environment in contrast to the iron age of the framing dialogue; and shows that although the world Diggon describes in "September" is the antithesis of that depicted in the "April" ode, Roffyn in actuality, and Hobbinoll and Diggon in potentiality, represent the forces (seen as another Saturn-Venus combination) that can effectively reconstruct the world in imitation of the peace, harmony, justice, mercy, friendship, and liberality of the "April" ode. Chapter V examines Mercurial motifs in "Maye., and August": the stress in "Maye's", debate on the duties and responsibilities of the clergy, particularly with respect to worldly wealth and to preaching ability and debating skills, is suitable to Mercury's rulership, as is the emphasis on fraud, deceit, and wealth in Piers' tale; Mercury's gift of verbal skill and dexterity is manifested in both the roundelay and the sestina in "August" Since the sun signifies things spiritual, while the moon is an age-old symbol of material mutability, "Julye" appropriately deals with ecclesiastical matters and "June" with secular; the two eclogues are complementary discussions of the moral and practical problems for the poet and priest of prominence or aspiration. Chapter VI shows that Spenser handles the themes of prominence and aspiration in ways suitable to the celestial governors of these eclogues: the sun and Leo are consistently associated with the ambitious or pre-eminent and with the perils and temptations besetting them, so "Julye's " debate covers these subjects and provides a catalogue of notable men; the most wellknown properties of the moon and Cancer (e.g., the moon's inconstancy and its shining by borrowed light and the sun's reversal of direction in Cancer) do not augur well for any ambitious impulse, so in "June" neither speaker is ambitious and Colin provides a bewildering series of rationalizations to justify his loss of aspiration. The concluding chapter suggests some possibilities for further study.
The Shepheardes Calender
Keywords: Shepheards Calender; Astrological Lore